BRCA1 and BRCA2 Variation in Taiwanese General Population and the Cancer Cohort - Chian, Jiasheng; Sinha, Siddharth; Qin, Zixin; Wang, San Ming (Frontiers in Molecular Biosciences, 2021)
BRCA1 and BRCA2 (BRCA) play essential roles in maintaining genome stability. Rapid evolving of human BRCA generates oncogenic variants causing high cancer risk. BRCA variation is ethnic-specific in reflecting adaptation and/or effects of genetic drift. Taiwanese population of 23.8 million is an admixture of multiple ethnic origins; Taiwan’s subtropical and tropical climate and geographically islandic location provide a unique natural environment. Therefore, Taiwanese population provides an unique model to study human BRCA variation. Through collecting, standardizing, annotating and classifying publicly available BRCA variants derived from Taiwanese general population and cancer cohort, we identified 335 BRCA variants, of which 164 from 1,517 non-cancer individuals, 126 from 2,665 cancer individuals, and 45 from both types of individuals. We compared the variant data with these from other ethnic populations of mainland Chinese, Macau Chinese, Japanese, Korean, Indian, and non-Asians. We observed that the sharing rates with other Asian ethnic populations were correlated with its genetic relationship. Over 60% of the 335 Taiwanese BRCA variants were VUS, unclassified variants or novel variants, reflecting the ethnic-specific features of Taiwanese BRCA variation. While it remains challenge of classifying these variants, our structural analysis predicted their enrichment of BRCA deleterious variants. We further determined the 3.8% prevalence of BRCA pathogenic variants in Taiwanese breast cancer cohort, and determined 0.53% prevalence of the BRCA pathogenic variants in Taiwanese general population, with the estimated 126,140 BRCA pathogenic variant carriers. We identified BRCA2 c.5164_5165delAG at BRCA2 BRC6 motif as a potential founder mutation in Taiwanese population. Our study on BRCA variation in Taiwanese and other east Asian populations demonstrate that ethnic-specificity is a common phenomenon for BRCA variation in east Asian populations, the data generated from the study provide a reference for clinical applications in BRCA-related cancer in Taiwanese population.